Pemberdayaan Ekonomi Kelompok Tani Tunas Baru Desa Sejahtra Astra Dusun Telaga Kodok Desa Hitu Lama, Maluku Tengah - muspida, Muspida; Ega, L; Ferdinandus, Stenly J; Christianty, Restia; Wenno, Meiske; Faisal, Muhammad; Sinay, Lexy Janzen; Borel, Aryanto; Regar, Erfendi; Arifin, Hasmia Melati; Souhoka, Semuel (Jurusan Matematika FMIPA Universitas Pattimura, 2024)
Agricultural development, as a component of national development, has an important role in the recovery of the national economy. This strategic function focuses on increasing regional income, providing food and industrial raw materials, increasing exports and foreign exchange, creating jobs and business opportunities, increasing farmers' income, and improving community welfare. One of the challenges farmers face is a lack of negotiating power. Consolidating farmers into one forum can strengthen negotiating power and integrate economic movements from pre-production to marketing. The activities carried out also experienced several business obstacles experienced by the business group, including climate and weather and Hurricane Lanina, which hit the Central Maluku region and its surroundings, causing disruption to organic vegetable production. DSA Telaga Kodok does not yet have a post-harvest packaging house, so it is difficult to obtain organic certification. The organic certificate has expired, so currently, farmer market partners have not received vegetables from DSA Telaga Kodok.